A review and prospective of fin design to improve heat transfer performance of latent thermal energy storage. (June 2023) - Zhang, Shengqi; Mancin, Simone; Pu, Liang
Abstract: Latent Thermal Energy Storage (TES) has been widely recognized in the academic community and regarded as one of the most promising technologies for heat storage. As one of the most efficient TES systems, finned-tube TES, including annular, helical and longitudinal fins, have been intensively investigated in terms of principles, materials, and optimization. A review study of the last decade is performed to show the evolution of finned-tube TES technology, and to pave the path of future development in this field. Firstly, the Phase Change Materials (PCMs) used in latent TES are summarized, and their thermal conductivity is reviewed and analyzed. Secondly, various fin shapes including annular, helical, longitudinal and topologically optimized are reviewed and evaluated, aiming at providing fundamental information and limitations of every shape and evaluating some possible perspectives to facilitate further developments. The comprehensive literature review indicated that longitudinal and annular fins have been the focus for the last decade or so. While helical fins and topologically optimized fins show the greatest research potential and can become an emerging hot topic due to their better performance as compared to traditional fin shapes. In addition, it appears that the heat transfer enhancement of latent TES system by fins alone is limited. Thus, additional enhancement techniques, such as magnetic fluid, bubble-driven flow, metal foam, nanoparticle and ultrasonic vibration can further improve the heat transfer rate of PCMs. This work aims to facilitate the advancement of finned-tube TES technologies. Highlights: PCMs used in latent TES are reviewed and analyzed. Reviews and evaluations on various fin types and topology optimized fin were performed. Recommendations for the future studies on implementing finned tubes were proposed. Topology optimization can be considered the most advanced fin design methodology. The entire cycle of energy storage must be the focused.